ASSESSING WRITING OF EFL STUDENTS OF AKADEMI MARITIM NUSANTARA CILACAP - Dhion Meitreya Vidhiasi (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2019)
English as a foreign language is always be considered a difficult language to be learned. There are four language skills that must be mastered, those are listening, reading, speaking, and writing. Writing is the most difficult skill to be learned among those four. In order to know the mastery of writing ability, assessment should be done. Assessing writing sometimes difficult to be done because the lecturer does not know what to be done and how to assess writing ability. This paper attempts to help the lecturer understand the key factors in assessing writing called validity and reliability. The goal of this paper is to enrich the knowledge of the lecturer about the technique of assessing writing.